Prevalence and Determinants of Mobile Health Applications Usage: A National Descriptive Study - Amer, Samar A.; Bahumayim, Ayah; Shah, Jaffer; Aleisa, Nouf; Hani, Basma M.; Omar, Doaa I. (Frontiers in Public Health, 2022)
We aimed to determine the prevalence of MHAs' usage and explore the context and determinants of using MHAs among inhabitants in Saudi Arabia (SA). This cross-sectional study randomly selected 679 adult inhabitants from the 20 health regions in SA through an electronic, self-administered, well-structured, and validated Arabic questionnaire. The prevalence of using MHAs was 47.9%, and it was significantly higher among younger, Saudis, highly educated, and working participants, as well as those with chronic diseases (p < 0.05). The main motives for using MHAs were to promote health status (68.6%) and to lose weight (33.2%). The most used apps were related to daily steps-counting (54.2%), and among females was tracking ovulation period apps (43.5%). The most common reported advantage of using MHAs was saving time (64%). Despite the potential benefits of MHAs, they were used by only about half of the study participants in SA. The most effective MHAs in improving health status were exercise, calorie-related, water uptake, and daily steps-counting apps. Policymakers looking to address reform aimed at improving health with mobile apps will find our study interesting.